Energy, security, and economic development in East Asia (St. Martin's Press, 1986)
This study examines the likely security consequences of the continued growth in energy. consumption in East Asia, and in particular: The dimensions of that growth which are likely to have an effect on international security. The dependencies and insecurities created by that continued growth. The policy guidance that can be derived for the United States from a review of those dependencies and insecurities.